1994
DOI: 10.1111/j.1939-165x.1994.tb00675.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Manatee Leukocytes Using Peroxidase Stain

Abstract: Leukocytes of the manatee, dog, cat, horse, rabbit, bird, and human were stained with modified Wright-Giemsa stain and myeloperoxidase stain. The predominant segmented leukocyte of the manatee stained positive for myeloperoxidase in a manner similar to the human, dog, cat, and horse neutrophil. Rabbit and bird heterophils stained unlike the manatee predominant leukocyte with myeloperoxidase stain. Eosinophils of all species examined also stained differently from the predominant manatee leukocyte. We conclude t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Dugong heterophil counts in our study often approximated lymphocyte counts, as has also been observed in Florida manatees; however, heterophils were the predominant circulating leukocyte in approximately one‐third of dugongs. Withstanding some variation in intensity of staining, dugong heterophils appear cytochemically similar to neutrophils in most mammalian species, and to heterophils in manatees and elephants, but are cytochemically dissimilar to heterophils in most avian and reptilian species . Ultrastructural examination of heterophils revealed a heterogeneous granule population predominated by round, oval, or rod‐shaped types, similar to those described for the Florida manatee .…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Dugong heterophil counts in our study often approximated lymphocyte counts, as has also been observed in Florida manatees; however, heterophils were the predominant circulating leukocyte in approximately one‐third of dugongs. Withstanding some variation in intensity of staining, dugong heterophils appear cytochemically similar to neutrophils in most mammalian species, and to heterophils in manatees and elephants, but are cytochemically dissimilar to heterophils in most avian and reptilian species . Ultrastructural examination of heterophils revealed a heterogeneous granule population predominated by round, oval, or rod‐shaped types, similar to those described for the Florida manatee .…”
Section: Discussionmentioning
confidence: 53%
“…Dugong monocytes were the largest circulating leukocyte and morphologically similar to monocytes of other species. Cytochemically, dugong monocytes lacked the PER and SBB staining reported in monocytes for other species, including manatees and elephants . Low numbers of circulating basophils were seen, and when observed, were well granulated, dissimilar to the reportedly sparsely granulated basophils of manatees .…”
Section: Discussionmentioning
confidence: 70%
“…However, blood reference ranges or values can di er among populations of the same species and vary according to age, sex, diet, environment, physiological conditions, and activity level. e hematology and blood chemistry of various Antillean manatee populations have been documented for Guyana [7], Mexico [8], Belize [9,10], Brazil [11][12][13][14], and for the Florida subspecies (T. manatus latirostris) [6,[15][16][17][18][19][20][21][22][23][24][25]. However, this has not been ascertained for Antillean manatees inhabiting the Greater Antilles.…”
Section: Introductionmentioning
confidence: 99%
“…PMNs of most marine mammals have round to oval granules that either do not stain or stain as pale pink within heterophilic granulocytes using Wright-Giemsa [75,77]. These heterophilic granules contain myeloperoxidase (MPO) and neutrophil elastase (NE), which are also typical terrestrial mammalian PMN-derived antimicrobial proteins, identified in PMNs of humans, horses, cattle, goats, and dogs [80,81,82,83,84].…”
Section: Cetacean/pinniped Leukocytes Of the Innate Immune Systemmentioning
confidence: 99%